Ethnobotany in Annapurna Conservation Area (ACA), Nepal: A Review - Poudel, Ashish; Gurung, Shila; Bhandari, Jyoti (Ethnobotany Research and Applications, 2022)
Background: Nepal is considered as a biodiversity hotspot with a multi-dimensional social system accompanied by vast amounts of plants and traditional knowledge regarding ethnobotanical practices. There are number of ethnic groups in Nepal whose culture is enriched by ethnobotanical knowledge that has been passed down over generations. Also, ethnobotanical knowledge is diverse in different regions of Nepal. The ethnobotany of Nepal and related archaic knowledge are of great importance to the advancement of local, national and global human society. In this study, we analyze ethnobotany in five districts within Annnapurna Conservation Area, Nepal’s largest protected area. Methods: Information was extracted from relevant publications from the year 1995 to 2021 from electronic databases following the PRISMA framework. Those extracted data from thirty-two publications were analyzed systematically. Results: This study revealed that the temporal research trend has varied significantly and that the number of research in the accessible areas were relatively higher. Despite the high occurrence of research focusing on ethnomedicinal uses, other ethnobotanical research focusing on Non-timber forest products, wild edible foods are still lacking. Conclusions: Priority should be given to relatively unexplored research topics and lesser explored areas such as wild edible foods and non- timber forest products, and pharmacognosy in the future, so that the research gap will be addressed which ultimately brings out the real potentiality of the ethnobotanical sector of Annapurna Conservation Area. Keywords: Ethnobotany, Annapurna Conservation Area, Nepal, Review